Novel α-Mangostin Derivatives from Mangosteen (Garcinia mangostana L.) Peel Extract with Antioxidant and Anticancer Potential - Vy Anh Tran; Thu-Thao Thi Vo; My-Nuong Thi Nguyen; Nguyen Duy Dat; Van-Dat Doan; Thanh-Quang Nguyen; Quang Hieu Vu; Van Thuan Le; Thanh Danh Tong (Journal of Chemistry)
The mangosteen peels contain biologically active compounds, with antioxidant and anticancer properties. Among these isolated phytochemicals, α-mangostin is one of the most powerful natural antioxidants and anticancer compounds. This study focused on synthesizing novel α-mangostin (α-MG) derivatives at positions of C-3 and C-6 from extracted α-MG of mangosteen peels and investigating antioxidant and anticancer activities. The structures of the synthesized compounds were determined by using MS, 1H-NMR, 13C-NMR, and HPLC. The analysis of the interaction between structure and bioactivity showed that phenol groups on C-3 and C-6 positions play a crucial role in antiproliferative activity to boost both anticancer efficacy and drug-like properties. The antioxidant activity of α-MG and its derivatives were investigated by the DPPH method. Among α-MG derivatives, 1-hydroxy-7-methoxy-2,8-bis(3-methylbut-2-en-1-yl)-9-oxo-9H-xanthene-3,6-diyl bis(2-bromobenzoate) (compound 4) exhibited significant antioxidant property. The in vitro cytotoxicity against various cancer cell lines (HeLa, MCF-7, NCI–H460, and HepG2) was evaluated by the standard sulforhodamine B assay. The anticancer activities (HeLa, MCF-7, NCI–H460, and HepG2) of compound 4 are five to six times higher than those of α-MG and other derivatives. The acetylation at C-3 and C-6 of α-MG by halogen of benzoyl greatly improved cancer cell toxicity. Our results provide new opportunities for further explorations of α-MG derivatives for antioxidant property and promise as drugs in cancer therapy.